2019
DOI: 10.1111/jscm.12203
|View full text |Cite
|
Sign up to set email alerts
|

How Supplier Economies of Scale Drive Supplier Selection Decisions

Abstract: Supplier selections are complex but nonetheless strategically important decisions that are influenced by numerous factors. Drawing on the resource‐based and relational view of the firm, we investigate how suppliers’ economies of scale influence the buyer's selection decision, and we illustrate how the influence of scale is contingent upon important economic, buyer, and relationship characteristics. We test the model with a large secondary dataset of actual supplier selection decisions from the automotive indus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 161 publications
0
26
0
Order By: Relevance
“…To make a broader generalization, it would be important to effectively argue that the theoretical mechanisms that bring about the observed relationships in the current sample also likely hold outside the sampling frame. As an example, a recent study by Badorf et al (2019) used RBV to examine how economies of scale influence the supplier selection decision, contingent on several moderating variables that serve as boundary conditions. Although they used a secondary database exclusive to the automotive industry, they cautiously note the same results could be generalizable to other industries.…”
Section: Research Design Considerations With Archival Datamentioning
confidence: 99%
“…To make a broader generalization, it would be important to effectively argue that the theoretical mechanisms that bring about the observed relationships in the current sample also likely hold outside the sampling frame. As an example, a recent study by Badorf et al (2019) used RBV to examine how economies of scale influence the supplier selection decision, contingent on several moderating variables that serve as boundary conditions. Although they used a secondary database exclusive to the automotive industry, they cautiously note the same results could be generalizable to other industries.…”
Section: Research Design Considerations With Archival Datamentioning
confidence: 99%
“…The supplier selection literature shows that selection decisions have significant implications for firms (e.g., Badorf, Wagner, Papier, & Hoberg, 2019; Kannan & Tan, 2002). To test our proposition that Systematic Selectors select more suitable new venture suppliers, future research should choose a longitudinal design to investigate whether Systematic Selectors ’ buyer–supplier relationships are more successful than those of other archetypes.…”
Section: Discussionmentioning
confidence: 99%
“…Whether in manufacturing, distribution, retail, or utilities, the basic aim of inventory analysis is to determine (1) when goods should be ordered and ( 2) how bulky the order should be. Badorf et al (2019), identified five factors for stock holding: Economies of scale; maintaining inventory allows a company to achieve economies of scale in production, buying, and transportation. When a company buys in bulk, it receives volume discounts.…”
Section: The Concept Of Inventory Managementmentioning
confidence: 99%
“…In periods of high inflation or as a deliberate strategy of speculation, elevated setup costs, for example, support manufacturing a higher number of units after the setup has been made and protect against anticipated shortages and price rises. Flow-through warehousing, according to Badorf et al (2019), aims to reduce inventory keeping (carrying) costs increasing the pace at which finished products are distributed.…”
Section: The Concept Of Inventory Managementmentioning
confidence: 99%